A THE ROLE OF COOPERATION IN ENGLISH CLASSES: THE ROLE OF COOPERATION IN ENGLISH CLASSES - Tajimbetova, Gulmira (Журнал иностранных языков и лингвистики, 2022)
Cooperation learning is one of the varieties of a student-centered approach in teaching a foreign language, which involves the organization of groups of students working together to solve a problem, topic, issue. Training tasks are structured in such a way that all team members are interconnected and interdependent, and at the same time quite independent in mastering the material and solving problems. The main idea of this technology is to create conditions for active joint learning activities of students in different learning situations.